SELF-CONTROL WITH ONLINE SHOPPING CONSUMPTIVE BEHAVIOR IN UIN SULTAN SYARIF KASIM RIAU STUDENTS - Charollina, Fuji Fira; Herwanto, Jhon (Persepsi: Jurnal Riset Mahasiswa Psikologi, 2024)
Abstract This study aims to determine the relation between self-control with consumptive behavior on online shopping among college students at State Islamic University of Sultan Syarif Kasim Riau. The population in this study were active college students from State Islamic University of Sultan Syarif Kasim Riau who had conducting online shopping’s activities. Total samples in this research were 255 respondents. This research used quantitative method with simple linear regression analysis technique and accidental sampling. Data were collected using Consumptive Behavior Scale and Self-Control Scale. The results showed a negative relationship between self-control and consumptive behavior on online shopping among college students at State Islamic University of Sultan Syarif Kasim Riau.